(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Students acquire knowledge through both life and school. Learning through life is informal while learning through school is formal education. The knowledge gained from life is not divided into any subject compartments but the knowledge imparted in school is limited to various subjects. Knowledge is basically integrated. In school, however, knowledge is presented to students through impenetrable compartments of subjects. This method of education is called ’subject wise method of education’. Most of the primary school students experience various problems in studies due to the subject wise method. They mainly include the lack of continuity in the learning experience, learning in a mechanical way according to the school timetable, lack of life experiences in the learning process, lack of subject correlations, the same concept being presented in different ways in different subjects, etc. Subject wise education does not expose students to the integrated nature of knowledge, students feel that there is a gap between school learning and real life, students are unable to establish correlation between school learning and real life.